Issues and Uses of Online Job Portals: A Comparative Study from the Perspective of Recruitment Consultants in Gujarat - Jayswal, Mitesh; Shukla, Kinjal; Heda, Nidhi (Prabandhan: Indian Journal of Management, 2015)
Purpose: The purpose of this paper was to compare the leading online job portals Naukri.com and Monster India on the basis of their operational difficulties and features from the perspective of recruitment consultants of Gujarat state. Design/Methodology/Approach: The paper presented a descriptive cross sectional survey of the employees working in recruitment consultancies in Gujarat. With the help of an in-depth interview of experts, operational difficulties and features were identified and their performance was compared using independent sample t-test. Major Findings: Reset problem, per click rate, and non-availability of niche profile were the problems faced by the consultants while using Naukri.com; whereas, catching the exact keywords, non availability of resumes, nationality not specified, and incomplete personal details were the problems faced by the consultants while using Monster India. Compared to Naukri.com, Monster India was considered better in searching for HR related articles, while Naukri proved better for business development and expansion. Originality/Value: The paper will be of value to those interested in recruitment activities, recruitment consultancy as a business, and online job portals as a business. It is suitable for academics and practitioners alike.